Natural environments, nature relatedness and the ecological theater: connecting satellites and sequencing to shinrin-yoku. Issue 1 (December 2015) - Craig, Jeffrey; Logan, Alan; Prescott, Susan
Abstract Recent advances in research concerning the public health value of natural environments have been remarkable. The growing interest in this topic (often housed under terms such as green and/or blue space) has been occurring in parallel with the microbiome revolution and an increased use of remote sensing technology in public health. In the context of biodiversity loss, rapid urbanization, and alarming rates of global non-communicable diseases (many associated with chronic, low-grade inflammation), discussions of natural vis-a-vis built environments are not merely fodder for intellectual curiosity. Here, we argue for increased interdisciplinary collaboration with the aim of better understanding the mechanisms—including aerobiological and epigenetic—that might help explain some of the noted positive health outcomes. It is our contention that some of these mechanisms are related to ecodiversity (i.e., the sum of biodiversity and geodiversity, including biotic and abiotic constituents). We also encourage researchers to more closely examine individual nature relatedness and how it might influence many outcomes that are at the interface of lifestyle habits and contact with ecodiversity.